2012
DOI: 10.1161/atvbaha.111.239046
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Thrombin Receptor Signaling on α-Smooth Muscle Actin + CD34 + Progenitors Leads to Repair After Murine Immune Vascular Injury

Abstract: Objective-The goal of this study was to use mice expressing human tissue factor pathway inhibitor (TFPI) on ␣-smooth muscle actin (␣-SMA) ϩ cells as recipients of allogeneic aortas to gain insights into the cellular mechanisms of intimal hyperplasia (IH ϩ cells were mobilized in significant numbers after allogeneic transplantation, the majority showing sustained expression of tissue factor and protease-activated receptor-1 (PAR-1). In WT, most were CD45 ϩ myeloid progenitors coexpressing CD31, vascular endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…12 Simply, a 5-mm segment of the infrarenal donor (MIF −/− mice, 15 C57BL/6 [Harlan Olac, Bicester, UK] mice, α-TFPI-Tg mice, or mice deficient in PAR-1 or -2 [The Jackson Laboratory]) aorta, flushed with 300 μL saline containing 50 U heparin, was transplanted into ApoE −/− recipients. Blood flow was confirmed by direct inspection after clamp removal.…”
Section: Aortic Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Simply, a 5-mm segment of the infrarenal donor (MIF −/− mice, 15 C57BL/6 [Harlan Olac, Bicester, UK] mice, α-TFPI-Tg mice, or mice deficient in PAR-1 or -2 [The Jackson Laboratory]) aorta, flushed with 300 μL saline containing 50 U heparin, was transplanted into ApoE −/− recipients. Blood flow was confirmed by direct inspection after clamp removal.…”
Section: Aortic Transplantationmentioning
confidence: 99%
“…10,12,17 Briefly, tissues were snap-frozen in dry ice, embedded in optimum cutting temperature compound (VWR International, Dorset, UK), sectioned at 5-μm thickness, and fixed in methanol at -20°C. Frozen sections were immersed in 1% BSA-PBS for 30 minutes and then incubated overnight at 4°C with the antibodies defined in the online-only Data Supplement.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever the source, a recent study demonstrated that targeting SM-α-actin and CD34-expressing cells could inhibit intimal hyperplasia and promote regenerative repair of the artery. 41 Thus, targeting these SM-α-actin and CD34-positive cells may be a potential treatment to prevent atherosclerosis, this may be especially relevant in patients with lupus with elevated levels of IFN-I.…”
Section: Discussionmentioning
confidence: 99%
“…4 In this regard, many recent publications in ATVB have provided further insight into the functional role of stem/ progenitor cells in (1) rescuing ischemic tissues, [5][6][7][8][9][10] (2) the stem cell-derived smooth muscle accumulation in neointima, and (3) the stem cell differentiation into vascular lineages. [11][12][13][14] In the present article, we will highlight these recent publications within a brief context of the literature on vascular stem/ progenitor cells.…”
mentioning
confidence: 99%